2020
DOI: 10.1371/journal.pone.0227464
|View full text |Cite
|
Sign up to set email alerts
|

PolyQ-independent toxicity associated with novel translational products from CAG repeat expansions

Abstract: Expanded CAG nucleotide repeats are the underlying genetic cause of at least 14 incurable diseases, including Huntington's disease (HD). The toxicity associated with many CAG repeat expansions is thought to be due to the translation of the CAG repeat to create a polyQ protein, which forms toxic oligomers and aggregates. However, recent studies show that HD CAG repeats undergo a non-canonical form of translation called Repeat-associated non-AUG dependent (RAN) translation. RAN translation of the CAG sense and C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…In line with this observation, the 13S and 13L peptides we used in this study were aggregated before their introduction to cells and when the aggregates were taken up by the recipient cells, they exerted toxicity to multiple types of cells. In contrast, it was reported that only polyL was consistently toxic across multiple types of cells, although all RAN polypeptides successfully formed aggregates in the C. elegans model 38 . Therefore, the formation of aggregates in endogenous RAN proteins does not seem to be the sole determinant of toxicity.…”
Section: Discussionmentioning
confidence: 85%
“…In line with this observation, the 13S and 13L peptides we used in this study were aggregated before their introduction to cells and when the aggregates were taken up by the recipient cells, they exerted toxicity to multiple types of cells. In contrast, it was reported that only polyL was consistently toxic across multiple types of cells, although all RAN polypeptides successfully formed aggregates in the C. elegans model 38 . Therefore, the formation of aggregates in endogenous RAN proteins does not seem to be the sole determinant of toxicity.…”
Section: Discussionmentioning
confidence: 85%
“…A more recent study examined the toxic effects of all six repeat peptide products of CAG-related RAN translation, including polyglutamine in C. elegans , and reported polyleucine to convey the strongest toxicity, which caused the most penetrant phenotype of stunted growth and defective motility in worms [ 71 ]. This result corroborated the previous finding in HD human brains that an alternative mechanism might be responsible for the neurotoxicity of CAG-repeat-related neurodegenerative diseases other than the conventionally thought polyQ repeats [ 71 ].…”
Section: Polyglutamine (Polyq) Repeat Diseasesmentioning
confidence: 99%
“…These contained codon-varied tags and different CAG-repeat lengths. This study showed that only the polyL protein induced significant toxicity depending on the CAG-repeat length, although all RAN translation proteins aggregated [ 70 ]. In contrast, different results were observed in the brains of two different mouse models: (1) a model that enabled RAN translation but did not express HTT with the polyglutamine tract translated from the start codon, and (2) a model that expressed N-terminal polyglutamine HTT.…”
Section: Aberrant Translationmentioning
confidence: 99%